Unlocking the Jaw - Improving Quality of Life in Bilateral Fibrous Ankylosis of the Mandibular Condyle with Dual Surgical Approach : A Case Report: Membuka Kunci Rahang - Meningkatkan Kualitas Hidup pada Ankylosis Fibrosa Bilateral Kondil Mandibula dengan Pendekatan Bedah Ganda: Laporan Kasus - Marini Sundari; Eka Marwansyah Oli`i; Endang Sjamsudin (Jurnal Kolaboratif Sains, 2026)
Fibrous ankylosis of the mandibular condyles restricts jaw movement due to fibrous tissue adhesions in the temporomandibular joint (TMJ), leading to impaired oral function. Surgical management, especially condylectomy and coronoidectomy procedures, remains the most effective method of improving jaw function. A 12-year-old girl with a history of facial trauma and previous surgical intervention who developed progressive limitation in mouth opening over last three years. Clinical examination showed complete inability to open the mouth. Cone Beam Computed Tomography (CBCT) confirmed bilateral fibrous ankylosis of the mandible. The patient underwent bilateral preauricular surgical approaches, with excision of fibrous adhesions, bilateral condylectomies, and unilateral coronoidectomy. Mersilene mesh was placed bilaterally. Intensive physiotherapy was initiated after the surgery. At six months follow-up, the patient demonstrated significant improvement in jaw mobility. Fibrous ankylosis of the mandibular condyles can severely limit jaw function, especially in growing children. Surgical management successfully released the ankylosis and restored mandibular movement. Placement of Mersilene mesh helped prevent re-ankylosis, while early and intensive physiotherapy played a crucial role in maintaining postoperative mouth opening. Comprehensive surgical management combined with intensive postoperative rehabilitation is essential for effective treatment in patients with bilateral fibrous ankylosis of the mandibular condyles